Evaluation of gas and particle sensors for detecting spacecraft-relevant fire emissions. (May 2020) - Wang, Xiaoliang; Zhou, Hao; Arnott, W. Patrick; Meyer, Marit E.; Taylor, Samuel; Firouzkouhi, Hatef; Moosmüller, Hans; Chow, Judith C.; Watson, John G.
Abstract: Fire detection faces challenges of increasing sensitivity, accuracy, and response speed while reducing false alarms. Air quality sensors measure fire emission signatures similar to smoke detectors but are often more sensitive. Recent advancement in air quality sensors provides an opportunity to improve fire detection. This study used low-cost and research-grade gas and particle sensors to detect and characterize emissions from laboratory smoldering and flaming tests of three spacecraft-relevant materials. The electrochemical carbon monoxide (CO) sensor sensitively detected fire emissions in all but a pyrolysis test, whereas the metal oxide volatile organic compound (VOC) sensor with cross sensitivity for CO detected fire emissions in all tested cases. Several low-cost particle sensors, although saturated at high concentrations, detected smoke at low concentrations. A combination of CO/VOC and particle sensors would provide sensitive fire detection distinct from non-combustion nuisance sources. In support of the ongoing Spacecraft Fire Safety Experiments (Saffire), the DustTrak DRX aerosol monitor was evaluated for smoke measurement. It measured particle concentrations over a wide range and its single particle counting provided additional size distribution data similar to that of an optical particle counter. However, the single particle counting accuracy degraded at high concentrations due to coincidence errors. Highlights: Fire emission signatures vary with fuels and combustion conditions. Air quality sensors can sensitively detect smoke at obscuration below 0.1%/m. Low-cost particle and CO/VOC sensors can be selective and sensitive smoke detectors. Spectral scattering and absorption properties vary with fuels and combustion phases. DRX single particle counting provides size distribution at low concentrations.